(untitled) (Research, Society and Development, 2021)
The aim of this study is to describe the socio-demographics characteristics and clinical features according to the different types of birth (vaginal and caesarean section) and health care system (SUS or private) in a cohort of puerperal women from a public hospital located in the west of Santa Catarina state. This is a retrospective, descriptive and transversal study, elaborated from the data of a cohort of women who gave birth by vaginal or caesarean delivery and who were admitted in a referral hospital in the west of Santa Catarina State. The data from medical records, stored in the hospital own network, was collected between November 2019 and March 2020. The variables analysed were: race/skin colour/ethnicity, age, marital status, health system (SUS or private), number of pregnancies, delivery route, use of episiotomy, laceration (categorized in second or third degree), maternal comorbidities, complications of delivery and prophylactic antibiotic therapy. The results showed that the majority of women were between 26 and 30 years of age, were white, married or in a stable relationship, pregnant for the second or third time, never had a miscarriage, developed complications during the current pregnancy, did not have intrapartum intercurrences, utilized public health system to grant access to medical care, did not undergo episiotomy and did not have any type of perineal tears during childbirth. These results show an abusive use of caesarean section, mainly in private care system; nevertheless, the rate of episiotomy is in accordance with the Wold Health Organization recommendation.